Organocatalyzed efficient one-pot synthesis, biological evaluation, and molecular docking studies of 4,4-(Arylmethylene)bis-(3-methyl-1-phenyl-1H-pyrazol-5-ols) - Mahajan, Pravin S.; Nikam, Mukesh D.; Khedkar, Vijay; Jha, Prakash; Badadhe, Pravin V.; Gill, Charansingh H. (Journal of Heterocyclic Chemistry, 2017)
The synthesis of 4,4-(arylmethylene)bis-(3-methyl-1-phenyl-1H-pyrazol-5-ol) derivatives catalyzed by ?-proline is a simple, versatile, and efficient method. In vitro antioxidant, anti-inflammatory, and antimicrobial activities of compounds 4a, 4b, 4c, 4d, 4e, 4f, 4g, 4h, 4i, 4j were studied. Furthermore, to rationalize the observed anti-inflammatory activity data, molecular docking study has been performed against COX-2 enzyme which revealed a good binding affinity for these molecules and could provide an insight into the various bonded and non-bonded interactions guiding their binding affinity.